Study on the contact behavior of pipe and rollers in deep S-lay. (March 2018) - Liang, Hui; Yue, Qianjin; Lim, Gerry; Palmer, Andrew C.
Highlights: We proposed a refined contact model to study the contact behavior between the pipe and rollers in deep S-lay. Our model got more reasonable and detailed results than the traditional design/analysis tools. The effects of stinger stiffness and rollerbox rotation on the contact force distribution were studied. The contact behaviors between the pipe and multiple rollers in one rollerbox were studied. Abstract: S-lay is a widely used method for offshore pipe installation. In recent years, S-lay has gradually applied to the deepwater condition. Because of the increasing pipe weight in deep S-lay, there exist severe and complex contact problems between the overbend pipe and roller supports of the stinger. In deep S-lay design, it is difficult to solve this nonlinear mechanics problem, and there remain confusion and difficulties to predict the roller contact forces and the pipe strain level in S-lay design. The present paper develops a refined finite element model with the framework of ABAQUS, which considers the complex surface contact behaviors in the overbend section. The features of the contact state of different rollers within one roller box are discussed, and the resultant support forces from each roller box are calculated and compared with the commercial design code. The overbend strain level of five S-lay cases is investigated and the pipelaying safety is checked by DNV rules. The simulation results show that the proposed model can provide more accurate and reasonable predictions on roller forces and pipe strain distribution for deepwater S-lay design.